Teaching elementary science and technology in Ontario - Malcolm Welch; David Barlex; Peter Chin; Cathy Christie; Andréa Mueller; Hugh Munby; Jenny Taylor (2000)
In 1998 the Ontario Ministry of Education and Training mandated a science and technology curriculum for all Grade 1-8 students. Its purpose is to provide students with the scientific and technological knowledge and skills that will enable them to be productive members of society, with the ability to identify and analyse problems, and with the ability to explore and test solutions in a wide variety of contexts. This paper describes an approach to teaching elementary science and technology developed through a partnership between a Faculty of Education and three local school boards. The approach has at its centre the concept of a Big Task, a significant activity which requires the use of knowledge, understanding and skill that has been taught in an integrated and holistic way. For students to be successful in a Big Task they need particular and appropriate knowledge, skill and understanding. These are taught through a series of Support Tasks: short, highly structured and focused activities.